Comparative Genomics of Facultative Bacterial Symbionts Isolated from European Orius Species Reveals an Ancestral Symbiotic Association - Chen, Xiaorui; Hitchings, Matthew D.; Mendoza, José E.; Balanza, Virginia; Facey, Paul D.; Dyson, Paul J.; Bielza, Pablo; Del Sol, Ricardo (Frontiers in Microbiology, 2017)
Pest control in agriculture employs diverse strategies, among which the use of predatory insects has steadily increased. The use of several species within the genus Orius in pest control is widely spread, particularly in Mediterranean Europe. Commercial mass rearing of predatory insects is costly, and research efforts have concentrated on diet manipulation and selective breeding to reduce costs and improve efficacy. The characterisation and contribution of microbial symbionts to Orius sp. fitness, behaviour, and potential impact on human health has been neglected. This paper provides the first genome sequence level description of the predominant culturable facultative bacterial symbionts associated with five Orius species (O. laevigatus, O. niger, O. pallidicornis, O. majusculus, and O. albidipennis) from several geographical locations. Two types of symbionts were broadly classified as members of the genera Serratia and Leucobacter, while a third constitutes a new genus within the Erwiniaceae. These symbionts were found to colonise all the insect specimens tested, which evidenced an ancestral symbiotic association between these bacteria and the genus Orius. Pangenome analyses of the Serratia sp. isolates offered clues linking Type VI secretion system effector–immunity proteins from the Tai4 sub-family to the symbiotic lifestyle.